(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The search for express and reliable methods of assessing the ecological state of ecosystems polluted by xenobiotics is one of the most urgent tasks of scientists of ecologists. Phytotesting and phytoindication of contaminated ecosystems is one of the promising methods satisfying the above requirements. Methods of phytotesting of soils contaminated with oil products is an actual direction in the assessment and remediation of contaminated soils. One of the objects of scientific interest is oil-contaminated soil in Balykchy city. As a result of leakage from the pipe of the oil depot in Balykchy, in the late 90s of the last century, about 600 tonnes of oil products got into the ground. The problem remains actual till today, as no effective measures on cleaning and restoration of contaminated lands have been taken. It is of scientific interest to study and assess phytotoxicity of soils contaminated more than 30 years ago and to select optimal phytotest objects, both sensitive and resistant species.